Fabrication of multifunctional carbon/clay nanocomposites by recycling oil shale semi-coke waste for coloring and enhancing mechanical and aging-resistant properties of acrylonitrile–butadiene–styrene. (December 2022) - Wu, L.; Mu, B.; Yang, H.; Zhao, F.; Zhu, Y.; Wang, A.
Abstract: With the increasingly demanding of environmental regulations, the disposal and sustainable resource utilization of industrial solid waste have attracted much attention. The carbon/clay nanocomposites were successfully fabricated derived from oil shale semi-coke waste via NaOH-assisted hydrothermal technology for coloring and reinforcing of acrylonitrile–butadiene–styrene in this study. The obtained nanocomposites were characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, and energy dispersive spectroscopy. With the increase in the mass ratio of NaOH to oil shale semi-coke, kaolinite, quartz, and other minerals in oil shale semi-coke gradually changed to analcine-C to faujasite-Na to sodalite, while the morphologies of carbon/clay nanocomposites transformed from nanosheets to nanosheets/nanorods to nanorods. Different morphologies had different effect on the mechanical properties of ABS, and the mixed-dimensional morphologies of the nanocomposites obviously improve the mechanical performances due to their synergistic effect compared with sheet-like and rod-like carbon/clay nanocomposites, respectively. Furthermore, the incorporation of carbon/clay nanocomposites into acrylonitrile–butadiene–styrene also enhanced its aging-resistant properties compared with the pure acrylonitrile–butadiene–styrene. Therefore, this study provides a feasible approach to realize the resource and sustainable utilization of oil shale semi-coke solid waste as functional filler for polymers. Graphical abstract: Image 1 Highlights: Carbon/clay nanocomposites with different morphologies were fabricated using oil shale semi-coke The morphology of nanocomposites was related to the mass ratio of NaOH to oil shale semi-coke. The nanocomposites could be used as functional filler for coloring and reinforcing acrylonitrile–butadiene–styrene. Tensile and bending strength of acrylonitrile–butadiene–styrene composites increased by 8.62% and 31.16% than pure acrylonitrile–butadiene–styrene. This study provided a promising strategy for resource and sustainable utilization of oil shale semi-coke.